The Studies Of Ability To Cultivate Bananas In Protected And Coverless Conditions - خدام, منذر; ونوس, حسن (Latakia University Journal -Biological Sciences Series, 2021)
The Research Aims To Study The Ability For Cultivating Bananas In Protected And Coverless Conditions . It Contains Many Major Topics : First Of All The Marketing Ability Which Depends On Growing Requirement For Bananas All Over The Year . Second One Is The Social Ability Which Provides The Chance To Work In Agriculture , Transfer The Bananas And Distribution Them . Third One Is The Environmental Ability That Considers Bananas Are Useful For Nature And They Give It A beautiful View And They Don’t Pollute It . Fourth One Is The Financial Ability Which Is Throughout The Government Supporting . Finally The Economical Ability Which Is The Basic One Because It Includes Calculation Processes To Build A Plastic Hole Which Its Size Is 1100 Square Meters , Its Running Costs And Its Economical And Financial Results . In Total This Research Studies How Much Money Does This Trilogy Plastic Hole Cost To Cultivate Bananas Throughout Three Basic Steps . Firstly : The Costs Of Building This Hole Is 15080000 Syrian Pounds According To The Agricultural Research Center In Tartous Which Contains A Modify In Prices To Suitable These Days . Secondly : The Agriculture Costs Prove Than One kg Of Bananas Need At Most 707 Syrian Pounds , Were As The Price Of Bananas It 1600 Syrian Pounds In 2020 . Thirdly : In The Economical Calendar Which Does The Calculation Of Economical Indictors To Cultivate Bananas Inside The Protected And Coverless Conditions And Compare It With Its Similarities Of Other Agricultures . The Protected Conditions Consider That The Bananas Cultivation Has More Economical Efficiency Than Tomato Cultivation . The Coverless Conditions Prove That The Bananas Cultivation Has More Economical Efficiency More Than Citrus Fruits . This Shows The Importance Of Revive This Agriculture Because It Has An Economical Necessary Through Providing Its Needs Of Different Materials , Protect It Of Its External Rivalry And Support Its Finance .